Infaq Utilization Strategy in the MSME Empowerment Program at LAZISMU Ponorogo - Muhamad Rizal; Ahmad Agus Hidayat; Wildan Ainun Mardianto; Arif Zulfahmi Yusuf (Al Iqtishod: Jurnal Pemikiran dan Penelitian Ekonomi Islam, 2024)
Post-Covid-19 pandemic, SME actors have started to recover from their setbacks and strive to regain their position as a leading sector in advancing the economy. In this research, the Muhammadiyah Zakat, Infaq, and Sedekah Charity Institution (LAZISMU) in Ponorogo was chosen as the research site due to its empowerment activities for SMEs through its Empowerment of SMEs program using infak funds. This study aims to determine the strategies employed by LAZISMU Ponorogo in utilizing infak funds for the Empowerment of SMEs program, as well as to identify obstacles and propose solutions to address these issues. Using a qualitative descriptive approach, data was collected through observation, interviews, and documentation, analyzed using the SWOT analysis method. Ultimately, the researcher found that LAZISMU Ponorogo employs the following strategies to empower SMEs: 1) identifying SME potentials, 2) planning program creation, 3) program implementation, and 4) program supervision. Some challenges encountered in the implementation of the SME Empowerment program include: 1) the absence of standardized Operating Procedures (SOP) guidelines, 2) the lack of a specific program division, 3) fundraising that has not reached the target, and 4) the selection stage of prospective recipients. Solutions proposed are: 1) establishing standardized guidelines or Standard Operating Procedures (SOP), 2) creating a specific division for the SME Empowerment program, 3) conducting public awareness campaigns and collaborating with a wider audience, and 4) being selective in choosing prospective recipients.